In Vivo Study of Red Spinach Leaf Extract on the Excretory System of Paracetamol-induced Toxic Dose Wistar Rats - Setyawan, Haris; Tejosukmono, Ario; Yunianto, Irfan; Wulandari, Siska; Susilawati, Sonya Tri (Jurnal Sain Veteriner, 2025)
Paracetamol is an antipyretic and analgesic drug that is relatively safe to consume orally with the appropriate dose and can be obtained without a doctor's prescription. The antioxidant quersetin contained in red spinach leaves can bind free radicals and strengthen the antioxidant defense system in the body. This study was conducted to determine the histopathological view of liver and kidney Wistar rats induced by toxic dose of Paracetamol after administration of ethanol extract of red spinach leaves. This research method used 24 Wistar rat which were divided into 4 groups. Kontrol  (aquadest), KN (Paracetamol 0.5 g/kg BW), P1 (ethanol extract of red spinach leaves 0.4 g/kg BW and Paracetamol 0.5 g/kg BW) and P2 (ethanol extract of red spinach leaves 0.8 g/kg BW and Paracetamol 0.5 g/kg BW). The administration of the extract was carried out for 15 days with Paracetamol on the last 5 days. Euthanasia was performed on the 16th day and then made preparations of liver and kidney with paraffin method (Hematoxylin eosin). Data observed included hepatosomatic index, total and area of hepatocytes, total of liver and kidney necrosis cells, area of inflammatory cells, total and area of glomeruli, and area of hemorrhage. Observation data were analyzed using One-Way ANOVA and DMRT further test (P<0.05). The results showed that the dose of ethanol extract of red spinach leaves 0.4 g/kg BW was able to reduce hepatocyte area, the total of necrosis cells, the area of inflammation and protect the glomerulus (P < 0.05). The conclusion of this study is that ethanol extract of red spinach leaves at a dose of 0.4 g/kg BW can protect the liver and kidneys of Wistar rats induced by Paracetamol at a dose of 0.5 g/kg BW